Answer:
B. The zeros are -2/3 and -3 because y=(3x+2)(x+3)
Step-by-step explanation:
Given the equation:
![y=3x^2+11x+6](https://img.qammunity.org/2023/formulas/mathematics/high-school/akipkhopy4sipa6lkphkvwkz9zskdbf8fe.png)
To find the zeros, first, factorize the expression:
![\begin{gathered} y=3x^2+9x+2x+6 \\ y=3x(x+3)+2(x+3) \\ y=(3x+2)(x+3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/59wcpc8gay3gscnprs1s6u7jys4rcu3lvh.png)
Next, set the factored expression equal to 0.
![\begin{gathered} y=(3x+2)(x+3)=0 \\ \implies3x+2=0\text{ or }x+3=0 \\ 3x=-2\text{ or }x=-3 \\ x=-(2)/(3)\text{ or }x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/mmvbwgb1qldgcip270cribclb7r515jo4y.png)
Thus, the zeros are -2/3 and -3 because y=(3x+2)(x+3).
The correct choice is B.